Evaluation of a New Clinical Endpoint for Moderate to Severe Influenza Disease in Children: A Prospective Cohort Study. (14th November 2019) - Rao, Suchitra; Yanni, Emad; Moss, Angela; Lamb, Molly M; Schuind, Anne; Bekkat-Berkani, Rafik; Innis, Bruce L; Cotter, Jillian; Mistry, Rakesh D; Asturias, Edwin J
Abstract: Background: A moderate to severe (M/S) influenza clinical endpoint has been proposed in children, defined as fever >39°C, otitis media, lower respiratory tract infection, or serious extrapulmonary manifestations. The objective of the study was to evaluate the M/S measure against clinically relevant outcomes including hospitalization, emergency room visits, antimicrobial use, and child/parental absenteeism. Methods: We conducted a prospective observational study of children aged 6 months–8 years at the Children's Hospital Colorado emergency department (ED) and urgent care site during 2016–2017 and 2017–2018. Children with influenza-like illness (ILI) underwent influenza testing by polymerase chain reaction (PCR); children who tested positive and a subset of matched test-negative controls underwent follow-up at 2 weeks. The primary outcome was the proportion of children who were hospitalized. Secondary outcomes included recurrent ED visits, antimicrobial use, hospital charges, and child/parental absenteeism within 14 days. Results: Among 1478 children enrolled with ILI, 411 (28%) tested positive for influenza by PCR. Of children with influenza illness, 313 (76%) met the M/S definition. Children with M/S influenza were younger (3.8 years vs 4.8 years), infected with influenza A (59% vs 44%), and more frequently hospitalized (unadjusted risk difference [RD], 6.3%; 95% confidence interval [CI], 2.1–10.4; P = .03) and treated with antibiotics (unadjusted RD, 13.3%; 95% CI, 4.3–22.4; P < .01) compared to those with mild disease. Conclusions: Children with M/S influenza have a higher risk of hospitalization and antibiotic use compared with mild disease. This proposed definition may be a useful clinical endpoint to study the public health and clinical impact of influenza interventions in children. Clinical Trials Registration: NCT02979626. Abstract : Young children classified with moderate to severe influenza illness had a higher rate of hospitalization and antibiotic use, suggesting the clinical usefulness of this measure to study the public health impact of influenza interventions in children.